Analisis Karakteristik dan Peran Strategi Migrasi Domestik dan Internasional pada Penghidupan Rumah Tangga Migran (Studi Kasus: Desa Padas, Desa Jono, dan Desa Gawan, Kecamatan Tanon, Kabupaten Sragen) - Mada Sophianingrum; Prihadi Nugroho; Melisa Angelina (Department of Urban and Regional Planning, Diponegoro University, 2022)
Migration for rural communities is part of an adaptation strategy to deal with stresses and risks to their livelihoods. In fact, the rural agricultural sector is formidable compared to other sectors because it can survive and increase significantly even though the economy is being disrupted due to the Covid-19 Pandemic. This study aimed to analyze the role of migration strategies carried out by migrant households in Padas Village, Jono Village, and Gawan Village. The sustainable livelihood framework becomes a reference for assessing comprehensive household livelihood. This research uses a case study approach. In-depth data collection is carried out on migrants and migrant families with various migration characteristics. The results show that the migration strategy that occurs in Padas Village, Jono Village, and Gawan Village is influenced by the time of migration, differences in resources/livelihood capital characteristics, the context of vulnerability to livelihoods, and the migration strategy conducted. At the regional scale, although there are differences in the characteristics of resources/livelihood capital between the three villages, the role of migration remains the same. Meanwhile, the role of the migration strategy can be seen more clearly based on the time of migration that occurred in the three villages.